The Role of Islamic Education in the Prevention of Promiscuity in the 21st Century - Yuningsih Putri; Nuzulia Rahmawati; Asep Roni Muhayar; Khozin (AJIS: Academic Journal of Islamic Studies, 2025)
This study analyzes the strategic role of Islamic education in preventing the dynamics of promiscuity in the 21st century in Indonesia. Using a qualitative approach with a descriptive-analytical design, this study involves teachers and ustadz of Islamic Religious Education, students and students aged 15-22 years, parents, and religious leaders in various formal and non-formal Islamic educational institutions. Data were obtained through in-depth interviews, participant observations, and documentation studies, then analyzed using Miles and Huberman's thematic analysis model. The results of the study show that Islamic education plays a fundamental role in fortifying adolescents through three main pillars: faith as a spiritual foundation, sharia as a normative-practical guideline, and morals as a manifestation of values in daily behavior. Its effectiveness is influenced by the competence of educators, family support, a conducive social environment, and contextual learning strategies that integrate digital technology. Challenges include the rapid development of information technology, limited resources, and changes in social values that are increasingly permissive. This study concludes that the development of contextual curriculum, the improvement of educator competence, and the strengthening of the educational ecosystem based on school-family-community collaboration are key steps. The main contribution of this research is the presentation of an integrative model of Islamic education that is responsive to the challenges of the digital era and relevant to strengthening the character of the younger generation.